Study on sustainable development and construction of karst mountain city based on the concept of a sponge city. (1st September 2022) - Li, Yue; Geng, Huacai
Abstract: In recent years, there has been rapid urbanization development in China. The rapid expansion of cities and the increase in the proportion of the area of impervious surfaces have caused urban flooding problems. The karst area in Southwest China is characterized by a sensitive ecosystem, poor self recovery ability and typical karst development. The problems of a fragile and imbalanced water ecology are particularly prominent in karst areas, making it necessary to explore the applicability of the concept of sponge cities in such environments. This study reviews the technical ideas, methods and concepts of sponge cities in China and abroad in recent years. Guiyang, a typical karst mountain city in China, was taken as an example in this study. This was because Guiyang has special hydrogeological characteristics as well as the current urbanization development processes that are affecting the water resources and the environment in the region. It is believed that the construction of mountain sponge cities in karst areas should be mainly through source reduction, process control and end management, combined with intelligent construction methods. Focus should be on strengthening the prevention and control of soil erosion in key areas and risk areas and on properly handling the relationship between urban construction and water resources and ecological environment protection. HIGHLIGHT: This study provides construction ideas and technical reference for international peers who are committed to the study of urban sustainable development and land and water resources management, especially for how to deal with the relationship between mountain city construction and ecological environment protection of water and soil resources in karst areas.